2009
DOI: 10.1002/cphc.200800549
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orbital Interpretation of Magic Clusters with Non‐Magic Numbers

Abstract: Why are they magical? Mixed-metal clusters have very different electronic properties from simple metal clusters. The large MO splitting and reordering of Al clusters by Cs doping render the jellium description invalid and are responsible for the magic nature of the highly symmetric Al(12)Cs(-) and Al(11)Cs(2) (-) clusters (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In accordance with the spherical jellium model, [63] one would predict such a cluster to have a high(er) stability owing to the closed nature of its electronic shells. [10,64] Indeed, Leuchtner et al [65] demonstrated that whilst most aluminium clusters react strongly with oxygen, Al 13 À , Al 23 À and Figure 1. Optimised internal core-shell clusters.…”
Section: Structure and Energeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the spherical jellium model, [63] one would predict such a cluster to have a high(er) stability owing to the closed nature of its electronic shells. [10,64] Indeed, Leuchtner et al [65] demonstrated that whilst most aluminium clusters react strongly with oxygen, Al 13 À , Al 23 À and Figure 1. Optimised internal core-shell clusters.…”
Section: Structure and Energeticsmentioning
confidence: 99%
“…As such, there will undoubtedly be deviations in the number of electrons required for forming a closed shell on moving between the unique clusters. Recent examples of atypical magic clusters include [Al (10)(11)(12) Cs ] À anions, [10] in which doping or attachment of a few (Cs) atoms significantly alters the electronic structure (large molecular orbital splitting and reordering effectively renders the jellium model invalid) with magic behaviour rationalised through detailed analysis of molecular orbital perturbations, and clusters such as Pu@C 24 satisfying the 32-electron principle, that is, the number of valence electrons corresponding to fully occupied spdf subshells for the central metal atom. [11] Recent reviews of nanoparticles touch on aspects spanning the entire nanotechnology spectrum, from synthesis and characterisation to the applications of these unique materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the surprisingly large HOMO-LUMO gaps at 38 electrons which are observed in Al 13 + and Al 12 Cs − can be explained by the hybridization and splitting of the 2P z and 1F z 3 states from the 2P and 1F subshells, in which the 2P z state is pushed up in energy to the next shell, and 1F z 3 is stabilized through hybridization. 36,37 At lower energies, the 1D z 2 is pushed up in energy and the 2S 2 is stabilized, resulting in a pronounced gap at 18 electrons. This is also consistent with the twofold degenerate states below this gap having E 1 irreducible representations and the state above this gap having A 1 symmetry, as shown in Fig.…”
Section: While the Resistance Of Cual 22mentioning
confidence: 99%